Development of IOT-based smart laboratory system - Kong, Wai Kin (2024)
The COVID-19 pandemic has shown how crucial it is to avoid physical contact, particularly for healthcare professionals performing research and diagnosis. This project suggests creating an IoT Lab to reduce the risk of virus exposure during laboratory work. A key feature is integrating a robotic arm for contactless laboratory operations, managed wirelessly via an ESP WROOM 32 microcontroller. The IoT Lab uses a variety of sensors to increase safety and accuracy. The MQ-2 gas sensor identifies potentially dangerous compounds or smoke early. The DHT22 temperature and humidity sensor provides real-time environmental data for maintaining regulated experimental settings. An LDR sensor is also used to control the lab's illumination. The fan may be intelligently regulated using sensor data to control the airflow, and the relay module makes it possible to activate or deactivate the lamp remotely. The logic level converter is also used to convert the signal from 3.3V to 5V to avoid damaging the circuit board. The BLYNK software enables smooth remote monitoring and management of the system through a user-friendly smartphone application. Researchers and healthcare professionals may conveniently and safely use the robotic arm while monitoring sensor readings, starting tests, and initiating investigations from their mobile devices. The Fritzing program is used to design and prototype the circuit board during development, ensuring every component's best connection and operation. This iterative design approach guarantees the IoT Lab's dependability and sturdiness with a limited budget. Establishing an IoT lab that considerably reduces the danger of physical contact for medical professionals during experiments and diagnostics is the main point of this project. This project aims to revolutionize laboratory practices in COVID-19 or upcoming deadly virus outbreaks by integrating cutting-edge technologies, such as a robotic arm and a network of sensors, and by offering remote control through the BLYNK program.